Spatial PD‐L1, immune‐cell microenvironment, and genomic copy‐number alteration patterns and drivers of invasive‐disease transition in prospective oral precancer cohort. Issue 5 (3rd January 2023) - William, William N.; Zhang, Jianjun; Zhao, Xin; Parra, Edwin R.; Uraoka, Naohiro; Lin, Heather Y.; Peng, S. Andrew; El‐Naggar, Adel K.; Rodriguez‐Canales, Jaime; Song, Jaejoon; Gillenwater, Ann M.; Wistuba, Ignacio I.; et al.
Abstract: Background: Studies of the immune landscape led to breakthrough trials of programmed death‐1 (PD‐1) inhibitors for recurrent/metastatic head and neck squamous cell carcinoma therapy. This study investigated the timing, influence of somatic copy‐number alterations (SCNAs), and clinical implications of PD‐L1 and immune‐cell patterns in oral precancer (OPC). Methods: The authors evaluated spatial CD3, CD3/8, and CD68 density (cells/mm 2 ) and PD‐L1 (membranous expression in cytokeratin‐positive intraepithelial neoplastic cells and CD68) patterns by multiplex immunofluorescence in a 188‐patient prospective OPC cohort, characterized by clinical, histologic, and SCNA risk factors and protocol‐specified primary end point of invasive cancer. The authors used Wilcoxon rank‐sum and Fisher exact tests, linear mixed effect models, mediation, and Cox regression and recursive‐partitioning analyses. Results: Epithelial, but not CD68 immune‐cell, PD‐L1 expression was detected in 28% of OPCs, correlated with immune‐cell infiltration, 9p21.3 loss of heterozygosity (LOH), and inferior oral cancer‐free survival (OCFS), notably in OPCs with low CD3/8 cell density, dysplasia, and/or 9p21.3 LOH. High CD3/8 cell density in dysplastic lesions predicted better OCFS and eliminated the excess risk associated with prior oral cancer and dysplasia. PD‐L1 and CD3/8 patterns revealed inferior OCFS in PD‐L1 high intrinsic induction and dysplastic immune‐cold subgroups. Conclusion: This report provides spatial insight into the immune landscape and drivers of OPCs, and a publicly available immunogenomic data set for future precancer interrogation. The data suggest that 9p21.3 LOH triggers an immune‐hot inflammatory phenotype; whereas increased 9p deletion size encompassing CD274 at 9p24.1 may contribute to CD3/8 and PD‐L1 depletion during invasive transition. The inferior OCFS in PD‐L1‐high, immune‐cold OPCs support the development of T‐cell recruitment strategies. Abstract : This study provides early insight of PD‐L1– and cytotoxic T‐cell–centered immune profiles in preinvasive lesions and invasive‐disease transition. The authors report, within the unique context of a prospective study designed with a primary end point of invasive cancer, that the onset of a PD‐L1–mediated immune‐suppressive microenvironment can occur in premalignancy, a positive association between PD‐L1 expression in oral premalignant epithelium, high risk molecular features (i.e., 9p21.3 loss of heterozygosity status and polysomy), and inferior oral cancer‐free survival.